If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 2) = 110 Reorder the terms: (2 + x)(x + 2) = 110 Reorder the terms: (2 + x)(2 + x) = 110 Multiply (2 + x) * (2 + x) (2(2 + x) + x(2 + x)) = 110 ((2 * 2 + x * 2) + x(2 + x)) = 110 ((4 + 2x) + x(2 + x)) = 110 (4 + 2x + (2 * x + x * x)) = 110 (4 + 2x + (2x + x2)) = 110 Combine like terms: 2x + 2x = 4x (4 + 4x + x2) = 110 Solving 4 + 4x + x2 = 110 Solving for variable 'x'. Reorder the terms: 4 + -110 + 4x + x2 = 110 + -110 Combine like terms: 4 + -110 = -106 -106 + 4x + x2 = 110 + -110 Combine like terms: 110 + -110 = 0 -106 + 4x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '106' to each side of the equation. -106 + 4x + 106 + x2 = 0 + 106 Reorder the terms: -106 + 106 + 4x + x2 = 0 + 106 Combine like terms: -106 + 106 = 0 0 + 4x + x2 = 0 + 106 4x + x2 = 0 + 106 Combine like terms: 0 + 106 = 106 4x + x2 = 106 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 106 + 4 Reorder the terms: 4 + 4x + x2 = 106 + 4 Combine like terms: 106 + 4 = 110 4 + 4x + x2 = 110 Factor a perfect square on the left side: (x + 2)(x + 2) = 110 Calculate the square root of the right side: 10.488088482 Break this problem into two subproblems by setting (x + 2) equal to 10.488088482 and -10.488088482.Subproblem 1
x + 2 = 10.488088482 Simplifying x + 2 = 10.488088482 Reorder the terms: 2 + x = 10.488088482 Solving 2 + x = 10.488088482 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 10.488088482 + -2 Combine like terms: 2 + -2 = 0 0 + x = 10.488088482 + -2 x = 10.488088482 + -2 Combine like terms: 10.488088482 + -2 = 8.488088482 x = 8.488088482 Simplifying x = 8.488088482Subproblem 2
x + 2 = -10.488088482 Simplifying x + 2 = -10.488088482 Reorder the terms: 2 + x = -10.488088482 Solving 2 + x = -10.488088482 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -10.488088482 + -2 Combine like terms: 2 + -2 = 0 0 + x = -10.488088482 + -2 x = -10.488088482 + -2 Combine like terms: -10.488088482 + -2 = -12.488088482 x = -12.488088482 Simplifying x = -12.488088482Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.488088482, -12.488088482}
| 4X+205=2X+177 | | 6-x=20-2x | | 1/10(9+3)=1/4(2-a) | | 4X+62=7X+26 | | 3w+4-2w=6 | | x^2+x^3-80=0 | | 0.8+0.6x=0.5x | | (4x-7)/8+x=(4x+7)/4+1 | | 8n=27n-9 | | m^2-6m+11=0 | | 2((w-50)+w)=840 | | 30-8x=11+11x | | 2/3(3x+1) | | (2/3)(3x+1)=5 | | 2(4-3x)=15 | | 6-8x=5x-9x+10 | | 6a-8=40 | | 8x=8-4x | | -8x=8-4x | | -2x+14=9x | | 8x+8=-4x | | 8x+8=-4 | | x+(x*.2)=45000 | | 5x^2+x+5y^2+6y-8=0 | | -5x-31=54-10x | | 4x+9x-40=80-7x | | -2x+14+3x=5+x+9 | | 20k+60=10k+100 | | 125m-75m+42750=45450-175m | | ((180+w)+w)2=1060 | | 125m-75m+42750=45450-175 | | 10X-15=3(2X+3) |